Longitudinal auditory data of children with prelingual single-sided deafness managed with early cochlear implantation - Arras, Tine; Boudewyns, An; Swinnen, Freya; Zarowski, Andrzej; Philips, Birgit; Desloovere, Christian; Wouters, Jan; van Wieringen, Astrid (Scientific reports, 2022)
Individuals with single-sided deafness (SSD) have no access to binaural hearing, which limits their ability to localize sounds and understand speech in noisy environments. In addition, children with prelingual SSD are at risk for neurocognitive and academic difficulties. Early cochlear implantation may lead to improved hearing outcomes by restoring bilateral hearing. However, its longitudinal impact on the development of children with SSD remains unclear. In the current study, a group of young children with prelingual SSD received a cochlear implant at an early age. From the age of four, the children’s spatial hearing skills could be assessed using a spatial speech perception in noise test and a sound localization test. The results are compared to those of two control groups: children with SSD without a cochlear implant and children with bilateral normal hearing. Overall, the implanted group exhibited improved speech perception in noise abilities and better sound localization skills, compared to their non-implanted peers. On average, the children wore their device approximately nine hours a day. Given the large contribution of maturation to the development of spatial hearing skills, further follow-up is important to understand the long-term benefit of a cochlear implant for children with prelingual SSD.